Dexamethasone improves redox state in ataxia telangiectasia cells by promoting an NRF2‐mediated antioxidant response. (12th October 2016) - Biagiotti, Sara; Menotta, Michele; Orazi, Sara; Spapperi, Chiara; Brundu, Serena; Fraternale, Alessandra; Bianchi, Marzia; Rossi, Luigia; Chessa, Luciana; Magnani, Mauro
Abstract : Ataxia telangiectasia (A‐T) is a rare incurable neurodegenerative disease caused by biallelic mutations in the gene for ataxia‐telangiectasia mutated (ATM). The lack of a functional ATM kinase leads to a pleiotropic phenotype, and oxidative stress is considered to have a crucial role in the complex physiopathology. Recently, steroids have been shown to reduce the neurological symptoms of the disease, although the molecular mechanism of this effect is largely unknown. In the present study, we have demonstrated that dexamethasone treatment of A‐T lymphoblastoid cells increases the content of two of the most abundant antioxidants [glutathione (GSH) and NADPH] by up to 30%. Dexamethasone promoted the nuclear accumulation of the transcription factor nuclear factor (erythroid‐derived 2)‐like 2 to drive expression of antioxidant pathways involved in GSH synthesis and NADPH production. The latter effect was via glucose 6‐phosphate dehydrogenase activation, as confirmed by increased enzyme activity and enhancement of the pentose phosphate pathway rate. This evidence indicates that glucocorticoids are able to potentiate antioxidant defenses to counteract oxidative stress in ataxia telangiectasia, and also reveals an unexpected role for dexamethasone in redox homeostasis and cellular antioxidant activity. Abstract : In cell lines derived from patients with Ataxia‐Telangiectasia, the glucocorticoid analogue Dexamethasone promotes the activation of the transcription factor NRF2, which induces antioxidant gene expression and stimulates pathways involved in glutathione synthesis and NADPH production. This increases the reserves of these antioxidant compounds and decreases the levels of oxidant molecules.